The effect of enterprise risks management, innovation towards sustainable finance moderated by intellectual capital - Lusmeida, Herlina; Augustine, Yvonne (Technium Social Sciences Journal, 2022)
This study aims to find out how the influence of Enterprise Risk Management (ERM), innovation on Sustainable Finance in banking companies listed on the IDX for the 2017-2020 periods. By using a sample of 42 banking companies during the study period, then doing a regression analysis of the existing empirical model and MRA considering that this study uses moderating variables, then the panel data processing is carried out, then data processing from the sample used is carried out. The results obtained that ERM has a significant positive effect on SF, innovation has a significant positive effect on SF, IC has a significant positive effect on SF, while IC is unable to moderate a significant positive relationship between ERM and SF and IC is also unable to moderate a significant positive relationship between innovation and SF .